Determinant Factors of Money Management among Nigerian Undergraduates - Taibat Tunrayo Adebisi; Oluwatosin Salami Odunayo; Diana Arubayi Oritshegbemi; Johnson Winifred Oluwaseyi (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2020)
The study assessed money management on Nigerian undergraduates at the University of Ilorin, Nigeria. Six research questions and four hypotheses were formulated. Descriptive research of a survey type was adopted. There were 16 faculties with five were selected purposively. The snowball method was used to select the sample size from the total population. A self-structured questionnaire was used to elicit information from the participants. Data collected were analyzed using frequency and percentage, while hypotheses were tested using ANOVA at 0.05 level of significance. Based on the findings, the participants agreed that they had different sources of money to make use of with a grand mean score of 2.83, while the course of study, religious beliefs, relationship status, and lifestyle influenced their money management with grand mean scores 2.80, 2.56, 2.85 and 2.70 respectively. The research hypotheses depicted the insignificant effect on religious beliefs, lifestyle, and relationship status had on money management, but only the effect of undergraduates' course of study was significant, and thus, the hypothesis was rejected. Conclusively, every undergraduate should apply a good pattern of financial behavior for improvement and sensitize themselves on money appropriateness since they will become future managers and decision-makers that will generate future revenues.